Living Al-Qur’an dan Hadits Dalam Tradisi Pengajian Malam Senin Wage di Masjid Sirojuddin, Mancasan Lor, Sleman, Yogyakarta - Hazami, Muhammad Fauzan; Rachmawan, Nadia Fauziah; Prasetia, M Aziz (Pascasarjana IAIN Metro, 2024)
There is tradition by a group of people by conducting recitation only at the time of every Monday night wage. This recitation tradition is held at the Sirojuddin Mosque. Many people consider that the recitation every Monday night wage is done with special provisions and held on a sacred day according to belief. Therefore, this research was conducted to see how the history and implementation of the recitation every Monday night wage? What is the basis used to carry out this recitation tradition? What is the purpose and value contained in the recitation of the wage Monday night? The purpose of this study is to describe the traditions that have to provide an understanding to the community that each tradition has its own motives and goals so as not to blame each other. This research method is qualitative research with a phenomenological approach. This type of research is field research, using data collection techniques of observation, interviews, documentation and literature. The data analysis used is data reduction, data presentation and conclusion making. The results showed that the tradition of recitation on Monday night wage is a form of living the Qur'an and hadith in the community in the form of writing and oral. The motive behind the recitation tradition every Monday night wage is because of the agreement that occurs in the community